Nano Convergence - Kim, Ki-Bum
Nano Convergence is a peer reviewed, international and interdisciplinary research journal that focuses on all aspects of nano science and nanotechnology. Submissions are solicited in all topical areas, ranging from fundamental sciences of physics and chemistry of nanoscale materials to practical applications of such materials including devices, energy applications and fabrication. Nano Convergence offers express review and publication and is provided as open-access to readers, making all research results freely available online. Topics include: Nanoelectronics Nanophotonics Nanomaterials Nanoenergy & Nanoenvironment Nanofabrication & Nanocharacterization Nanobio & Nanomedicine Emerging Nanotechnology.